2018
DOI: 10.1037/xhp0000464
|View full text |Cite
|
Sign up to set email alerts
|

Spatial perspective taking mediated by whole-body motor simulation.

Abstract: Humans can envision the world from other people's viewpoints. To explore the embodied process of such spatial perspective taking, we examined whether action related to a whole-body movement modulates performance on spatial perspective-taking tasks. Results showed that when participants responded by putting their left/right foot or left/right hand forward, actions congruent with a movement's direction (clockwise/counterclockwise) reduced RTs relative to incongruent actions. In contrast, actions irrelevant to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 65 publications
(168 reference statements)
3
24
0
Order By: Relevance
“…Transformations of visuospatial images are important spatial abilities that play roles in a wide range of everyday activities, including tool use 2 , navigation 3,4 , social interactions [5][6][7] , and academic and occupational success [8][9][10] . Further, it is well known that mental transformations of visuospatial images are at least partially subserved by sensorimotor processes necessary for corresponding physical transformations [11][12][13][14][15][16] , consistent with embodied cognition theories 17,18 .…”
Section: Introductionsupporting
confidence: 62%
“…Transformations of visuospatial images are important spatial abilities that play roles in a wide range of everyday activities, including tool use 2 , navigation 3,4 , social interactions [5][6][7] , and academic and occupational success [8][9][10] . Further, it is well known that mental transformations of visuospatial images are at least partially subserved by sensorimotor processes necessary for corresponding physical transformations [11][12][13][14][15][16] , consistent with embodied cognition theories 17,18 .…”
Section: Introductionsupporting
confidence: 62%
“…Mental spatial transformations such as mental rotation (Shepard & Metzler, 1971) are closely linked to sensorimotor processing or embodied (e.g., Gardony, Taylor, & Brunyé, 2014;Muto, Matsushita, & Morikawa, 2018;Sekiyama, 1982;Wexler, Kosslyn, & Berthoz, 1998;Wohlschläger & Wohlschläger, 1998; for a review, Zacks & Michelon, 2005). Within a framework of embodied cognition, previous research has demonstrated repeatedly that the mental rotation of objects resembling human bodies was performed more quickly and with less errors than the mental rotation of abstract objects (a body analogy effect) using computer-based chronometric tasks (Amorim, Isableu, & Jarraya, 2006;Jansen, Lehmann, & Van Doren, 2012;Krüger, Amorim, & Ebersbach, 2014;Makinae & Kasai, 2017;Makinae, Yamazaki, & Kasai, 2015;Sayeki, 1981;Voyer & Jansen, 2016); moreover, similar effects were observed in studies using paper-and-pencil psychometric tests (e.g., Alexander & Evardone, 2008;Doyle & Voyer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, when participants proactively self-generate the response movement, initiation of the movement differed with foot movements occurring before finger movements. Pfister et al (2014) confirmed that finger responses initiate before foot movements due to shorter nerve conduction to the hand than foot, whereas other researchers have identified foot movements occurred before finger movements when self-determining the direction of motor simulation tasks (e.g., Brunia & Van den Bosch, 1984; Muto et al, 2018). Using these established different ipsilateral behavioural response patterns to unpredictable and self-generated tasks, it is possible to investigate the mental representation of imagery.…”
Section: Introductionmentioning
confidence: 56%